DIABETIC RETINOPATHY IN NEWLY DIAGNOSED DIABETES MELLITUS (The Research of Medical Science Review, 2025)
Objectives: To determine frequency of diabetic retinopathy in newly diagnosed cases of diabetes mellitus.Place and Duration of the study: Pakistan Institute of Medical Sciences, Islamabad from July-2024 to December-2024.Methodology: A total of 175 patients with newly diagnosed diabetes were included. They were assessed for presence of diabetic retinopathy thorough fundoscopic examination by consultant ophthalmologist to screen for presence and severity of diabetic retinopathy. Data was analyzed using SPSS version 20.Results: In this study, 175 patients were included. Median age was 45.00 (60.00 – 25.00) years. There were 89 (50.86%) male and 86 (49.14%) female patients. Median BMI was 31.60 (34.50 – 21.70) kg/m2. Median HbA1C% was 8.10 (12.60 – 6.80) %. Frequency of DR in newly diagnosed cases of diabetes in present study was 50 (28.57%). Amongst these patients with DR (n = 50), 22 (44.00%) were found to have mild non-proliferative DR, 15 (30.00%) had moderate non-proliferative DR, 8 (16.00%) had severe non-proliferative DR and 5 (10.00%) had proliferative DR.Conclusion: Frequency of diabetic retinopathy in newly diagnosed cases of diabetes was 28.57%.